(untitled) (Res Gesta, 2022)
The proposal of this article consists of investigating, from a political reading, the two editions of Argirópolis made by Sarmiento in 1850 and 1851. Examining the particularities of each version, I am interested in delving into two aspects. In the first place, to understand the content and the consequent objectives of Argirópolis based on the other sarmientine writings of the period, such as Facundo, La Crónica and Sud América. In relation to this, and as a second point to explore, I will problematize the place assigned by Sarmiento to the work in question, according to the interests pursued in the respective publication moment.